2023
DOI: 10.3390/catal13081206
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Difluorophenyl Substituents on Structural, Redox, and Magnetic Properties of Blatter Radicals

Abstract: Blatter radicals 1-(3,4-difluorophenyl)-(1a) and 1-(2,4-difluorophenyl)-3-phenyl-1,4-dihydrobenzo[e][1,2,4]triazin-4-yl (1b) were prepared in good yields through oxidation of the corresponding amidrazones using MnO2 in dry CH2Cl2. Cyclic voltammetry showed that both radicals are oxidized and reduced chemically and electrochemically reversibly in accordance with −1/0 and 0/+1 processes. EPR spectroscopy indicated that spin density is mainly delocalized on the triazinyl moiety of the heterocycle. The structure o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 80 publications
1
6
0
Order By: Relevance
“…Electronic absorption spectra (EASs) of both radicals 2a and 2b in acetonitrile at room temperature have quite intense absorption bands in the UV range with a maximum at 265 nm and a number of bands in visible and near-UV regions of much lower intensity (SI Figure S6). The observed spectra are characteristic of related 1,4-dihydrobenzo­[ e ]­[1,2,4]­triazin-4-yl radicals and as expected are very similar to those of the previously described difluoro derivatives 1b and 1c . EASs of the latter have been analyzed in detail before via time-dependent DFT calculations (see also details in SI).…”
Section: Resultssupporting
confidence: 76%
See 1 more Smart Citation
“…Electronic absorption spectra (EASs) of both radicals 2a and 2b in acetonitrile at room temperature have quite intense absorption bands in the UV range with a maximum at 265 nm and a number of bands in visible and near-UV regions of much lower intensity (SI Figure S6). The observed spectra are characteristic of related 1,4-dihydrobenzo­[ e ]­[1,2,4]­triazin-4-yl radicals and as expected are very similar to those of the previously described difluoro derivatives 1b and 1c . EASs of the latter have been analyzed in detail before via time-dependent DFT calculations (see also details in SI).…”
Section: Resultssupporting
confidence: 76%
“…It was demonstrated that the existence of two fluorine atoms in the phenyl substituent exerts a substantial influence on the packing mode of the paramagnetic materials and on their magnetic characteristics. Magnetic susceptibility assays indicated that in both crystals, radical···radical exchange interactions are strong and have an AF nature with J / k B = −292 or −222 K, which is substantially greater than that of nonfluorinated analog 1a ( J / k B = −2.2 K) . Hence, the introduction of F atoms into 1,4-dihydrobenzo­[ e ]­[1,2,4]­triazin-4-yls can be an effective way to influence intermolecular magnetic couplings.…”
Section: Introductionmentioning
confidence: 99%
“…The UV-Vis spectrum of the BltÀ F 2 was recently calculated using the time-dependent DFT, and the structure of the spectrum in the near-UV-visible region (300-700 nm) was predicted to be due to the superposition of absorption bands into a series of ~20 excited states. [27] It is clear that NN substituents also contribute to the spectrum of the tetraradical, for example, phenyl-substituted nitronyl nitroxide has the following spectral data in ethanol: 238 (9.4×10 3 ), 263 (1.22×10 4 ), 360 (1.33×10 4 ), and 588 (0.69×10 3 ). [50] Note that spectral data for the BltÀ (NN) 2 triradical in dichloromethane are also known, λ max /nm (ɛ max /L mol À 1 cm À 1 ): 303 (3.49×10 4 ), 371 (2.26×10 4 ), 510 (5.26×10 3 ), and 545 (5.24×10 3 ).…”
Section: Electrochemistry and Uv-vis Spectroscopymentioning
confidence: 99%
“…[21] Another exceptionally stable radical is the 1,2,4-benzotriazinyl radical synthesized by Blatter et al [22] (Blt radical). This type of radicals is currently gaining increasing importance due to the proposed efficient synthetic strategies, [23][24][25][26][27] which have paved the way for multifunctional paramagnetic agents with interesting magnetic properties. [28,29] Stable radical units have the distinct advantage that they can be attached to any organic moiety and can even be purified and crystallized under ambient conditions.…”
Section: Introductionmentioning
confidence: 99%
“…So far, various nitronyl nitroxides have been created to construct heterospin molecule-based magnetic systems, but a comprehensive series of paramagnetic metal ions' complexes with fluorinated radicals has not been investigated. Naturally, it is to be expected that the introduction of fluorine into metal-radical systems can have a major effect on their packing in crystals, thus altering intermolecular exchange interaction channels and ultimately the parameters of magnetic materials [26][27][28][29][30][31].…”
Section: Introductionmentioning
confidence: 99%